THE THEORY OF INTRODUCING INNOVATIONS IN THE SUSTAINABLE DEVELOPMENT OF SMALL BUSINESS ENTITIES AND ITS CHARACTERISTICS - Rustamov Alisher Rakhmatullaevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article presents ideas and considerations about the theory of introducing innovations in the sustainable development of small business entities and its specific features.